(untitled) (IPS Journal of Education, 2025)
This quasi-experimental study evaluated the effects of delaying school start times from 8:00 a.m. to 10:00 a.m. on attendance, illness-related absences, and academic performance among Junior Secondary School 1 (JSS 1) and Senior Secondary School 1 (SSS 1) students during Arcadia Park Academy’s Summer Holiday Program from August to September 2024 in Ibadan, Nigeria. Using an A-B-A design across three program sessions, data were collected on daily attendance, verified illness absences, standardized exam scores, and student-reported sleep and alertness. Illness-related absences decreased by 32% among JSS 1 and 50% among SSS 1 students during the delayed start session (both p < .01). Concurrently, exam scores improved by 10% for JSS 1 and 12% for SSS 1 students (p < .05). Upon returning to the original start time, absenteeism and academic performance approached baseline values. These findings align with international research advocating alignment of school schedules with adolescent biological rhythms to enhance health and educational outcomes. The study offers empirical evidence to inform educational policy reforms in Nigeria, especially in supplementary educational programs.